Estimation of Secondary Organic Aerosol Formation During a Photochemical Smog Episode in Shanghai, China. Issue 7 (6th April 2020) - Wang, Hongli; Wang, Qian; Gao, Yaqin; Zhou, Min; Jing, Shengao; Qiao, Liping; Yuan, Bin; Huang, Dandan; Huang, Cheng; Lou, Shengrong; Yan, Rusha; de Gouw, Joost A.; et al.
Abstract: Secondary organic aerosols (SOA) are formed through diverse processes in the atmosphere, among which photochemical processing is one important pathway. SOA formation was studied based on one heavy photochemical smog episode in summer in Shanghai. During the pollution episode, ozone and organic carbon (OC) increased simultaneously with a strong positive correlation, which was complete opposite to the volatile organic compounds (VOCs) pattern but similar to that of VOC photochemical consumption. The OC evolution was explained well by a parameterization method based on the observation of OC and VOCs, and secondary OC (SOC) formation was derived, being comparable with the result based on elemental carbon (EC) tracer method. About 67% of SOC could be explained by the photochemical consumption of VOCs (mainly aromatics, ~93%) during the episode. The contribution of VOCs to SOC formation was also estimated from the available VOC emissions inventories, which was comparable with that based on VOCs observations in ambient. Some differences of VOC species contribution to SOC were found between the ambient observation‐based and the emission‐based results, and the contribution of C9 aromatics was underestimated in the emission inventory. This suggests that bias of speciation might exist in the current VOC emissions inventories. The present study highlights the importance of VOC oxidation for SOC formation in summer in Shanghai. More insights are needed to improve the accuracy of VOCs speciated emissions inventories. Key Points: OC correlated well with ozone during a photochemical pollution episode The OC atmospheric evolution was explained by a parameterization method The photochemical consumption of VOCs accounted for 67% of SOC formation